A multi-objective mixed integer programming model for multi echelon supply chain network design and optimization - Paksoy, T.; Özceylan, E.; Weber, G.-W. (Системні дослідження та інформаційні технології, 2010)
This paper applies a mixed integer linear programming to designing a multi echelon supply chain network (SCN) via optimizing commodity transportation and distribution of a SCN. Proposed model attempts to aim multi objectives of SCN by considering total transportation costs and capacities of all echelons. The model composed of three different objective functions. The first one is minimizing the total transportation costs between all echelons. Second one is minimizing of holding and ordering costs in distribution centers (DCs) and the last objective function is minimizing the unnecessary and unused capacity of plants and DCs. Застосовується змішане лінійне цілочислове програмування до побудови багатоешелонної мережі поставок (SCN) за допомогою оптимізації перевезень і розподілу в SCN. Запропонована модель дозволяє враховувати багато задач SCN за допомогою розгляду загальних витрат на транспортування і місткості всіх ешелонів. У модель включено три різні цільові функції: перша — мінімізує повні вартості перевезень між усіма ешелонами; друга — мінімізує витрати від збереження і вартості замовлення в центрах розподілу (DCs), а остання цільова функція мінімізує зайву і невикористану потужність заводів і DCs. Применяется смешанное линейное целочисленное программирование к построению многоэшелонной сети поставок (SCN) посредством оптимизации перевозок и распределения в SCN. Предложенная модель позволяет учесть многие задачи SCN посредством рассмотрения общих затрат на транспортировку и емкостей всех эшелонов. В модель включены три различные целевые функции: первая — минимизирует полные стоимости перевозок между всеми эшелонами; вторая — минимизирует затраты от сохранения и стоимости заказа в центрах распределения (DCs), а последняя целевая функция минимизирует излишнюю и неиспользованную способность заводов и DCs.